ATURAN PEMODELAN KOMPUTASI UNTUK ELIMINASI SIGNAL SPEKTRUM-RF YANG TIDAK DIINGINKAN - Sirmayanti Sirmayanti (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2020)
One of the important mechanisms of the transmitter-receiver (Tx-Rx) digitization system through the RF upconverter is computation-based of the right solution to the harmonic problem. The cause of harmonics on the RF-spectrum in the RF upconverter architecture is the quantization process. Any change of frequency offsetting in the quantization rate causes interference so that an unwanted signal appears in the targeted signal. A number of harmonics appear also due to the rectangular nature during the pulse width / position modulation (PWM / PPM) process. To achieve the optimization of this unwanted signal elimination, it is necessary to have the right selectivity over sampling ratio (OSR) and precise techniques of using fc against the frequency clock (fclock). fclock is a determining factor for determining the number of points of quantization complexity because it is related to the representation of the phase level and amplitude of the signal. Therefore a computational rule is needed in predicting the size of the harmonic product and the harmonic elimination solution in this goal.